Author guidelines in dermatological journals discourage the use of the CAse REport guidelines. (1st October 2015) - Miguel, D.; Elsner, P.
Abstract: Linked Comment:  Garcia‐Doval, Br J Dermatol 2015; 173: 894–895 .